The monetary policy transmission mechanism channels efficiency in the Republic of Belarus - Kharitonchik, Anatoly I. (Journal of the Belarusian State University. Economics, 2020)
Understanding the functioning of the transmission mechanism is one of the most important elements for the implementation of an effective monetary policy. In the context of the National Bank of the Republic of Belarus gradual transition to the inflation targeting framework, the issue of increasing the efficiency monetary transmission is of particular relevance. To solve it at the initial stage, it is necessary to evaluate the efficiency of functioning of individual channels of the transmission mechanism, which is the aim of this study. Based on the construction of the semi-structural macroeconomic general equilibrium model for the Republic of Belarus, the contributions of individual transmission mechanism channels to the change in the main macroeconomic variables in response to monetary impulse are revealed. The results demonstrate the predominance of the interest rate channel in the dynamics of economic activity and the expectations channel in the dynamics of inflation in the Republic of Belarus.